Peran Madrasah Diniyah dalam Mengembangkan Kecerdasan Spiritual Siswa - Kunthi, Yulianisa Dewi; Istiqlaliah, Hulailah (An-Nuha, 2024)
Seeing the current era of globalization with the presence of criminal acts committed by children, Islamic Education Institutions are needed that develop children's spiritual intelligence by instilling spiritual values. Madrasah Diniyah is a community-based non-formal Islamic education institution that can provide religious education through the classical system in an integrated manner. This research aims to describe the role of Madrasah Diniyah in developing the spiritual intelligence of grade 4 students at MDA Al-Waajidul Iman. This research uses qualitative research. Data collection using observation, interviews and documentation. The results of this research show that MDA Al-Waajidul Iman in carrying out its role as an Islamic Education Institution can effectively develop the spiritual intelligence of students, this is proven by students who have a sense of responsibility as students of knowledge, have an attitude of trust in Allah, are honest, sincere, and serious in seeking knowledge. Even though there are aspects that need special attention, such as the flexible aspect, Madrasahs can overcome them through control and collaboration with parents.